Comparing the phenotypic, genotypic, and proteomic identification of Trichosporon species: A globally emerging yeast of medical importance - Lara, Bruna Rossini [UNESP]; De Camargo, Bruno Braidotti; Paula, Claudete Rodrigues; Junior, Diniz Pereira Leite; Garces, Hans Garcia [UNESP]; Arnoni, Mariana Volpe; Silveira, Mônica; Gimenes, Viviane Mazo Fávero; Siqueira, Lumena Pereira MacHado; Takahashi, Juliana Possatto Fernandes; Melhem, Márcia De Souza Carvalho; Richini-Pereira, Virgínia Bodelão; et al. (My University, 2021)
Trichosporon spp. are widely distributed in the nature, comprising species that inhabit different ecological niches and can be found in the water, soil, and body surface of animals and humans. Such microorganisms have been classically associated with superficial infections; however, in the last decades, they have also been related to disseminated infections in immunocompromised patients, behaving as opportunistic agents, which demands rapid and accurate species identification for efficient therapy. Concordance level between the traditional phenotypic method and the molecular technique (gold standard) in the identification of all 59 Trichosporon samples was 59.3%. Identification concordance between MALDI-TOF spectrometry and the molecular technique was 71.2%. No isolate of environmental origin was identifiable by MALDI-TOF mass spectrometry (MS), and 100% of such environmental isolates were discordant for IGS region sequencing and phenotypic characterization. Both comparisons evidenced greatest concordance in the identification of T. asahii. The species T. debeurmannianum, T. dermatis, T. venhuisii and T. insectorum were not properly identified by both MALDI-TOF MS and the phenotypic technique. MALDI-TOF MS, in particular, seems to be appropriate to investigate yeasts of the genus Trichosporon; however, database updates are still necessary, especially for species that are not common in the clinical routine. With the aim of helping understand the aspects involved in early and accurate diagnosis of infections caused by this opportunistic agent, the present study compared the phenotypic, molecular (IGS region) and mass-spectrometry (MALDI-TOF) identification of 59 yeasts of the genus Trichosporon which had clinical and environmental origin and were kept in a mycology collection.
Keywords: Emerging pathogens; Genotypic identification; MALDI-TOF MS; Phenotypic identification; Trichosporon spp